Natural polysaccharide-based hydrogel bioprinting for articular cartilage repair - Wu, Xuerui; Cheng, Xueliang; Kang, Mingyang; Dong, Rongpeng; Zhao, Jianwu; Qu, Yang (Frontiers in Materials, 2023)
Tissue engineering represents a promising approach for impaired articular cartilage tissue regeneration. 3D printed hydrogels have become an emerging tissue engineering strategy because they closely mimic the physical and biochemical characteristics of the extracellular matrix. The formulation of hydrogel ink holds significant importance in attaining a precisely defined scaffold, which could exhibit excellent shape fidelity post-printing. Natural polysaccharide-based hydrogels are a highly promising class of scaffold biomaterials for articular cartilage regeneration in the field of material science and tissue engineering. These hydrogels are particularly advantageous due to their exceptional water absorption capacity, biodegradability, adjustable porosity, and biocompatibility, which closely resemble those of the natural extracellular matrix. This review aims to provide a comprehensive overview of the key characteristics, functions, and research progress in 3D printing technology for natural polysaccharide-based hydrogels. Specifically, this review categorizes the commonly used natural polysaccharide-based hydrogel materials in cartilage tissue engineering, and summarizes the classic literature in this area. In the end, we provide a comprehensive analysis of the challenges and potential applications of natural polysaccharide-based hydrogels in cartilage tissue engineering.